2012
DOI: 10.1002/ceat.201200268
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fischer‐Tropsch Process in a Fixed‐Bed Reactor Using Non‐uniform Catalysts

Abstract: Optimization of Fischer-Tropsch (FT) process in a fixed-bed reactor is carried out using non-uniform catalysts. The C 5 + yield of the reactions is maximized utilizing a combination of non-uniform catalysts across the bed. A 1D heterogeneous model is developed to simulate the bed containing uniform and non-uniform catalysts. It is found that the egg-shell and surface-layered catalysts result in higher C 5 + yield. Moreover, effects of cooling temperature are studied. Genetic Algorithm (GA) and Successive Quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, excessively high temperatures in the catalyst bed should be avoided for the sake of system safety and FTS reaction performance 5 . Temperature runaway, which is a serious issue in practice, was observed in Mazidi's research when the reaction heat was not immediately removed 6 . Dry 7 states that higher temperatures will result in higher selectivity toward undesired methane; while it was also found that the probability of chain growth decreases when the temperature increases 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, excessively high temperatures in the catalyst bed should be avoided for the sake of system safety and FTS reaction performance 5 . Temperature runaway, which is a serious issue in practice, was observed in Mazidi's research when the reaction heat was not immediately removed 6 . Dry 7 states that higher temperatures will result in higher selectivity toward undesired methane; while it was also found that the probability of chain growth decreases when the temperature increases 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches can be used to minimize transport limitations: egg-shell catalyst with a specific thickness of the active layer [14,15], wash-coated monoliths [16], solid foams, and micro-and millireactors. Mazdidi et al have demonstrated that, by using a tubular fixed bed reactor, it is convenient to use different catalyst distributions along the bed length, as the diffusion limitations strongly depend on the reactant conversion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the academic and industrial interest, the models reported on in the literature are based on a simplified approach. Boukezoula and Bencheikh [17] developed a steady-state modelling approach for the aromatization of methyl cyclopentane. Thus, all the dynamic aspects are neglected; that is an essential issue to be considered within the start-up operation of a chemical plant.…”
Section: Introductionmentioning
confidence: 99%
“…Also, due to lower catalyst loading, the inert pellet mixing also reduces the reactor performance [153]. In practice, the non-uniform catalysts are commonly seen on Fischer-Tropsch reactors for the optimization of hydrocarbon formation [156]. The bed temperature runaway is found to be completely prevented in the optimum case and the long chain hydrocarbon selectivity (C 5 + ) is enhanced [156].…”
Section: Axis Directionmentioning
confidence: 99%
“…In practice, the non-uniform catalysts are commonly seen on Fischer-Tropsch reactors for the optimization of hydrocarbon formation [156]. The bed temperature runaway is found to be completely prevented in the optimum case and the long chain hydrocarbon selectivity (C 5 + ) is enhanced [156]. On the steam methane reforming (the reverse of methanation) reactor, catalyst dilution by adsorbent is one of the useful reactor design strategies for the thermal optimization [150].…”
Section: Axis Directionmentioning
confidence: 99%